The Semognostics and its explorations' environment - Budrevičius, Algirdas (Information & Media, 1996)
Semognostics denotes a direction in science, which describes the meaning and knowledge phenomena, considering them both separately and as a complex meaning-knowledge, that is, a semognostic phenomenon. The term originates from Greek words semos and gnosis. The main idea of semognostics is to explain the intelligence on the basis of knowledge and meaning phenomena. More generally it may be viewed as a discipline for describing various nonphysical phenomena in terms of meaning and knowledge. By now, the exploration has been focused on explanation of the phenomena of human intelligence.Traditional phenomena, such as a mind, consciousness, memory and attention were considered. New phenomena were described, such as a potential intellectual energy and mind current.The second part of the article describes the context of the exploration and gives an author's evaluation of the investigation from various points of view.
Keywords: -